Proposed new interior design of Simplysiti Beauty Outlet for Simplysiti Sdn. Bhd at 176, Jalan Maarof, Bangsar, 59000, Kuala Lumpur / Ibnur Shahrizat Abdul Razak - Abdul Razak, Ibnur Shahrizat (Faculty of Architecture, Planning and Surveying, 2010)
Interior Design is one of the courses provided in Universiti Teknologi Mara (UiTM). In order to obtain the scroll of diploma, all final year students are required to prepare one final year project which is compulsory. The project must be relevant to be done based on few aspects such as the feasibility of the project and the current issue that support the project proposed. The students must perform at their best using all of the application learnt during first, second and the third year of study. There are lots of processes to be undergone which include research, case study, interviewing, designing a proposal, submission by stages, critique session, preparing art work, preparing presentation drawings, design development and final presentation. SimplySiti Sdn. Bhd is the client for this project. As the brand of SimplySiti is getting famous among Malaysians, it is a good investment of time to propose an outlet for SimplySiti. The reason for this proposal is because of few factors. First, SimplySiti is a new brand yet a big potential brand to stand in the same group of international brands. Second, Simplysiti is depending on other shops and outlets to sell their products. Yet, SimplySiti doesn’t have a permanent premise or selling floor for its own brand. The limitation of information and assistance provide the issue to the client. Having a single permanent premise will boost up the attention of the public because it will be the very first shop (premise) for SimplySiti. Then, the site chosen is located at 176, Jalan Maarof, Bangsar, 59000, Kuala Lumpur. It is private single building property owned by a fashion designer from Cambodia named Miss Sakinah Kosem.